Multicharacteristics optimization of electrical discharge micro hole drilling in Mg alloy using hybrid approach of GRA–regression–PSO. Issue 1 (6th July 2020) - Ahuja, Neeraj; Batra, Uma; Kumar, Kamal
Abstract : Purpose: Magnesium alloys are becoming prominent as an alternative to the permanent biomedical implants. In present work, electric discharge drilling (EDD) process has been investigated and optimized for ZM21 Mg alloy that can be used for producing perforated bone implants having geometrically precise micro holes. Design/methodology/approach: Planning of experiments has been carried out in accordance to the Taguchi mixed L18 orthogonal array (OA). The hole overcut (HO), circularity at entrance (Cent) and circularity at exit (Cext) of drilled micro holes were measured as response characteristics during experimentation corresponding to different settings of EDD input parameters. For optimizing multiresponse characteristics, the hybrid approach of grey relational analysis, regression analysis and particle swarm optimization has been implemented. Findings: It is found from hybrid approach that brass electrode along with Ip; 3 Amp, Ton; 50 µs and Toff; 52 µs outperformed over all other parametric settings against the collective result of response characteristics. The experimental values of response characteristics at suggested optimized setting are HO: 93.48 µm; Cent: 0.988 and Cext: 0.992, respectively. Originality/value: The optimization of EDD process for developing perforated Mg alloy bone implants, using hybrid approach is still missing.